Evaluating Stress during Pregnancy: Do We Have the Right Conceptions and the Correct Tools to Assess It?. (1st February 2018) - González-Ochoa, Raquel; Sánchez-Rodríguez, Elly N.; Chavarría, Anahi; Gutiérrez-Ospina, Gabriel; Romo-González, Tania
Abstract : Gestational stress is believed to increase the risk of pregnancy failure and perinatal and adult morbidity and mortality in both the mother and her child or children. However, some contradictions might arise from methodological issues or even from differences in the philosophical grounds that guide the studies on gestational stress. Biased perspectives could lead us to use and/or design inadequate/incomplete panels of biochemical determinations and/or psychological instruments to diagnose it accurately during pregnancy, a psychoneuroimmune-endocrine state in which allostatic loads may be significant. Here, we review these notions and propose a model to evaluate and diagnose stress during pregnancy.